Dos disparos - Pampín, Susana; Coelho, Benjamín; Federman, Rafael; Martelli, Manuela 1983-; Fabbri, Camila 1989-; Arenillas, Fabían 1963- (Just Entertainment, 2015)
Set in Argentina, 17-year-old Mariano finds a gun in his house and, in a thoughtless impulse, shoots himself twice. But he survives
Bildformat 16:9
Originally produced as a motion picture in 2014
Keywords: Teenagers / Argentina / Conduct of life / Drama; High school students / Drama; Parent and teenager / Argentina / Drama; High school students; Parent and teenager; Teenagers / Conduct of life; Argentina; Drama; Film; DVD-Video